ENVIRONMENTAL, DEMOGRAPHIC, AND SOCIO-ECONOMIC CORRELATES OF ACCESS TO IMPROVED SANITATION: EMPIRICAL EVIDENCE FROM PAPUA AND WEST PAPUA PROVINCES - Sri Irianti; Puguh Prasetyoputra (Research Centre for Population, Indonesian Institute of Sciences, 2015)
Papua and West Papua provinces are two of many lagging provinces in Indonesia in terms of access to adequate sanitation. Hence, this paper aims to reveal determinants of access to improved sanitation by investigating the environmental, demographic, and socio-economic correlation in both provinces. Data from the 2011 Multiple Indicator Cluster Survey (MICS) were used to determine the demographic and socio-economic correlates of households access to improved sanitation facilities. Probit regression models were fitted to the data. The results suggest that district, place or residence, type and location of household water source, household size, age of household head, education of household head, and household wealth have significant correlation with access to improved sanitation. These corroborate previous findings and more importantly, it can be used to inform policy makers in Indonesia especially in Papua and West Papua Provinces.Â